Specific cell-cell contact serves as the developmental signal to deactivate discoidin I gene expression in Dictyostelium discoideum - Berger, Edward A. (1983)
Specific cell-cell contact is a major regulatory signal controlling cell differentiation in Dictyostelium discoideum, causing dramatic changes in the developmental program of gene expression. In this report, we focus on the relationships between specific cell-cell contact and the activity of the genes for discoidin I, an endogenous lectin that has been implicated in the cell-cell cohesion process. By performing quantitative RNA dot-hybridization assays and RNA gel blot-hybridization analyses, using as a probe a recombinant plasmid containing a discoidin I cDNA insert, we have measured changes in discoiding I mRNA levels during normal development and in response to specific manipulations of the state of cellular aggregation. Our major findings are as follows. (i) During normal development on filters, there is a close temporal correspondence between the establishment of specific cell-cell contacts and the decline in discoidin I mRNA levels. By the tight-aggregate stage, discoidin I mRNA is barely detectable. (ii) When tight aggregates are disaggregated and the cells are maintained in the disaggregated state, there is a dramatic rise in discoidin I mRNA content. (iii) When cells are developed in suspension (conditions that interfere with the establishment of tight cell-cell contacts), discoidin I mRNA accumulates to abnormally high levels, and these persist well after the levels in filter-developed cells have declined. Taken together, these results strongly suggest that cell-cell contact is the normal developmental signal to deactivate discoidin I gene expression; thus, a contact-deactivated gene for which a recombinant DNA probe is available has now been identified. Furthermore, we demonstrate that exogenous cAMP almost completely blocks the disaggregation-induced reactivation of discoidin I gene expression. Possible mechanistic relationships between specific cell-cell contact, intracellular cAMP levels, and developmental gene expression are discussed.